Effect of some food sources associated with cassava in Africa on development success, fecundity, and longevity of Euseius fustis (Pritchard and Baker) (Acari: Phytoseiidae) - Bruce-Oliver, S.J.; Hoy, M.A.; Yaninek, John S. (1996)
Various foods associated with cassava were tested for their effect on the development, fecundity and longevity of Euseius fustis, the most common phytoseiid species found on cassava in Africa. Euseius Justis developed successfully to adulthood on the spider mite prey species Mononychellus tanajoa (Bondar) and Oligonychus gossypii (Zacher) and on pollen from maize, castor bean and cassava. Euseius Justis also completed development on water-diluted phloem exudate from cassava, diluted honeydew from the cassava mealybug and on various pollen and prey combinations. When reared on Tetranychus urticae Koch prey or free water only, E. Justis did not develop past the deutonymphal stage. All larvae held on clean leaf discs on water-soaked cotton died without moulting, suggesting that E. fustis must feed in order to moult to the nymphal stages. Diets of maize plus castor bean pollen and maize pollen plus M. tanajoa resulted in the highest rate of development, the highest fecundity and the greatest longevity. Castor bean pollen alone and maize pollen alone produced a higher fecundity and greater longevity than M. tanajoa tested alone. A colony of E. Justis reared continuously for seven generations on castor bean pollen produced nine times more adult females than a colony of E.fustis reared continuously on M. tanajoa. No negative effects on the development and fecundity of E. fustis were observed after seven generations were reared on pollen. Various foods associated with cassava were tested for their effect on the development, fecundity and longevity of Euseius fustis, the most common phytoseiid species found on cassava in Africa. Euseius Justis developed successfully to adulthood on the spider mite prey species Mononychellus tanajoa (Bondar) and Oligonychus gossypii (Zacher) and on pollen from maize, castor bean and cassava. Euseius Justis also completed development on water-diluted phloem exudate from cassava, diluted honeydew from the cassava mealybug and on various pollen and prey combinations. When reared on Tetranychus urticae Koch prey or free water only, E. Justis did not develop past the deutonymphal stage. All larvae held on clean leaf discs on water-soaked cotton died without moulting, suggesting that E. fustis must feed in order to moult to the nymphal stages. Diets of maize plus castor bean pollen and maize pollen plus M. tanajoa resulted in the highest rate of development, the highest fecundity and the greatest longevity. Castor bean pollen alone and maize pollen alone produced a higher fecundity and greater longevity than M. tanajoa tested alone. A colony of E. Justis reared continuously for seven generations on castor bean pollen produced nine times more adult females than a colony of E.fustis reared continuously on M. tanajoa. No negative effects on the development and fecundity of E. fustis were observed after seven generations were reared on pollen.